The impact of quality management systems on the effects of the process approach implementation - Alicja Gębczyńska; Radosław Wolniak (Economic and Environmental Studies (E&ES), 2019)
The article provides a discussion on results of extensive empirical research conducted in 2016 on a sample of 495 local government authorities, using the CAWI questionnaire technique supported by the CATI survey. The results thus obtained were verified in statistical terms and then critically analysed in a manner enabling final conclusions to be drawn. The purpose of the article is to analyse the impact of the quality management system (QMS) on the advantages and disadvantages identified as those which arise from the process approach implementation in public administration. Therefore the following principal research question may be posed: Is there a positive impact of the QMS on how well the process approach functions and to what extent does it affect the benefits and barriers involved in the process approach implementation? It has been observed that implementation of the quality system does not automatically guarantee any external benefits resulting from the process orientation. The research results imply that efficiency of the quality management systems implemented in the local government authorities subject to the survey is questionable, particularly in terms of their improvement.
Keywords: D73; H55; H83; 330; process approach; public administration; benefits and barriers of the process approach